2017
DOI: 10.1038/s41467-017-00900-1
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome in atherosclerotic cardiovascular disease

Abstract: The gut microbiota has been linked to cardiovascular diseases. However, the composition and functional capacity of the gut microbiome in relation to cardiovascular diseases have not been systematically examined. Here, we perform a metagenome-wide association study on stools from 218 individuals with atherosclerotic cardiovascular disease (ACVD) and 187 healthy controls. The ACVD gut microbiome deviates from the healthy status by increased abundance of Enterobacteriaceae and Streptococcus spp. and, functionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

59
849
5
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,185 publications
(1,014 citation statements)
references
References 63 publications
59
849
5
17
Order By: Relevance
“…coverage is required for obtaining resolutions down to species level, and there are concerns regarding reproducibility between the established sequencing platforms and computational tools. [38][39][40] The application of next-generation sequencing indicated numerous associations between gastrointestinal conditions and altered composition of the microbiome, for example in inflammatory bowel disease 41 and C difficile infection, 42 and a wide range of non-intestinal diseases such as type 1 and 2 diabetes, 43,44 liver and cardiovascular disease, 45,46 rheumatic diseases, 47 multiple sclerosis 48 and autism-spectrum disorders. 49 Microbiome compositions that differ from a balanced, healthy state are often referred to as dysbiosis, although there is no consensus on the composition of a eubiotic, healthy microbiome, nor is there a widely agreed definition of the term dysbiosis.…”
mentioning
confidence: 99%
“…coverage is required for obtaining resolutions down to species level, and there are concerns regarding reproducibility between the established sequencing platforms and computational tools. [38][39][40] The application of next-generation sequencing indicated numerous associations between gastrointestinal conditions and altered composition of the microbiome, for example in inflammatory bowel disease 41 and C difficile infection, 42 and a wide range of non-intestinal diseases such as type 1 and 2 diabetes, 43,44 liver and cardiovascular disease, 45,46 rheumatic diseases, 47 multiple sclerosis 48 and autism-spectrum disorders. 49 Microbiome compositions that differ from a balanced, healthy state are often referred to as dysbiosis, although there is no consensus on the composition of a eubiotic, healthy microbiome, nor is there a widely agreed definition of the term dysbiosis.…”
mentioning
confidence: 99%
“…In a new study published in Nature Communications , Jie and colleagues performed shotgun sequencing of the gut microbiome in a Chinese cohort of 218 patients with atherosclerotic cardio vascular disease (ASCVD) and 187 healthy controls 1 . They observed several significant associations between the microbiota taxa and disease status, strengthening the evidence for the inclusion of ASCVD in the ever-expanding list of microbiota- associated diseases.…”
mentioning
confidence: 99%
“…TMAO levels have been associated with ASCVD in a number of human studies, and animal model studies suggest that TMAO has a causal role in the disease 5,6 . Interestingly, Jie et al noted an association between copies of the bacterial genes encoding TMA lyases — the enzymes involved in TMAO generation — and ASCVD 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Jie et al demonstrated the relationship between the gut microbiota and atherosclerotic CVD. 9 They identified that the composition of gut microbiome, including members of the Enterobacteriaceae and Streptococcus spp, was higher in atherosclerotic CVD than in the healthy controls. 9 Karlsson et al used shotgun sequencing of the gut metagenome to reveal that intestinal microbial communities in patients with symptomatic atherosclerosis were different from those in healthy controls.…”
Section: Coronary Artery Diseasementioning
confidence: 99%